2020
DOI: 10.1002/nano.202000055
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials in wound healing: From material sciences to wound healing applications

Abstract: An increasing number of innovative therapies have emerged in the field of wound healing. Nanostructured systems have been used to improve wound healing at different stages. The drug itself may be formulated at a nanoscale such that it can function as its own "carrier" or nanomaterials may be used as drug delivery vehicles. The present work covers the latest advancements on innovative nano-based organic and inorganic materials. These novel drug delivery systems possess high stability, large surface area and tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 101 publications
0
48
0
Order By: Relevance
“…Nano‐materials with unique physical and chemical properties have received considerable attention in recent decades. [ 1–7 ] Its stability and duration are the most significant to design interfacial materials and micro‐electro‐mechanical systems, including superhydrophobicity, icephobicity, self‐cleaning, soft electronic circuits, and sensing systems. [ 8–14 ] However, the nano‐materials are always be ruined due to the base with weak mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nano‐materials with unique physical and chemical properties have received considerable attention in recent decades. [ 1–7 ] Its stability and duration are the most significant to design interfacial materials and micro‐electro‐mechanical systems, including superhydrophobicity, icephobicity, self‐cleaning, soft electronic circuits, and sensing systems. [ 8–14 ] However, the nano‐materials are always be ruined due to the base with weak mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well known that nanoparticles exhibit great benefits in accelerating wound healing, including re-epithelialization property, tissue adhesion, and differentiation. [49] According to our previous work, it was demonstrated that the catechol groups of PDA could scavenge radical and played a key role to accelerate the wound healing process. [37] In addition, the conductivity of PPy also plays a significant role in different stages of the wound healing process.…”
Section: In Vivo Wound Healing Performance and Histological Analysesmentioning
confidence: 99%
“…Prior to clinical evaluation of these wound-healing formulations, acceptability and efficacy must be assessed in comparison with conventional treatment options. Indeed, the most important steps in the development of wound care formulations are the evaluation of biocompatibility, antimicrobial activity and in vivo wound-healing activity [ 91 ]. Table 1 presents major newly developed formulations that are still to be fully assessed within pre-clinical studies.…”
Section: Health Benefits Of Bee Products With Focus On Regenerative Medicinementioning
confidence: 99%